Antioxidant properties of leaf and flower extracts of Moringa oleifera Lam (kelor) and their effects on acetaminophen-induced hepatotoxicity in vivo - Sharifudin, Syazana Akmal (2011)
Moringa oleifera Lam (MO) is a tropical plant and an important food commodity. The plant has garnered enormous attention recently due to its nutritional value. Malaysian Indian community used this plant traditionally for various therapeutic purposes. Despite many studies conducted on its hepatoprotective action, no study has been designed to address the question whether MO could work as an antioxidant and protect the liver concurrently with acetaminophen (APAP) intoxication. Therefore the aim of this study is to investigate the antioxidant activity of different parts of Moringa oleifera tree and the action of flowers and leaves hydroethanolic extract respectively in protecting the liver following concurrent treatment of high doses of APAP. Total phenolic content was conducted using Folin-Ciocalteu reagent and antioxidant assay was conducted using 1,1-diphenyl-2-picylhydrazyl (DPPH) free radical scavenging activity assay and ferric reducing antioxidant power (FRAP) assay of each part of the plant. A preliminary study was carried out to obtain the optimum dose for hepatotoxicity and the results will determined the dose of APAP in subsequent studies. The doses used were 2.0g of APAP/kg body weight, 4.0g of APAP/kg body weight and 6.0g of APAP/kg body weight via oral route. The study measured liver and renal function as well as histological changes in the liver and kidney. In hepatoprotective study, leaves and flowers hydroethanolic extract (200mg/kg body weight and 400mg/kg body weight, i.p) were administered an hour after APAP administration respectively. N-Acetylcysteine (NAC) was used as the positive control. Liver function tests, renal function tests, reduced glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), malondialdehyde (MDA), 4-hydroxynonenal (4-HNE) protein adduct were analysed and histological changes were compared between groups. The total phenolic content was the highest in the flowers followed by leaves. The result correlates (R2=0.8765) well with the antioxidant assay where flowers extract also showed the highest antioxidant capacity. Meanwhile, acetaminophen-induced hepatotoxicity increased the level of alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Blood urea nitrogen (BUN) as well as serum creatinine was observed to be normal indicating no kidney damage. The level of GSH, SOD and CAT were significantly decreased and the MDA and 4-HNE protein adduct levels were elevated in groups treated with APAP. Histologically, the liver was observed to have severe inflammation and bridging necrosis. When concurrent treatment was conducted with either flowers or leaves, the level of ALT and AST were significantly reduced. The results were consistent with histological observation. The liver sections obtained from rats treated with flowers and leaves hydroethanolic extract showed reduction in the severity of the liver damage. Serum BUN and creatinine were also decreased following plant extract treatment. The level of antioxidant enzymes such as SOD and CAT were found to have increased besides, GSH level was also enhanced. On the other hand, MDA and 4-HNE protein adduct were observed to be decreased. These results had indicated the possible action of hydroethanolic extract of MO flowers and leaves in protecting liver against over dosage of APAP.